AUTOMATED VERIFICATION OF ACTIVITY DIAGRAM USING UMLSEC ON XMI DATA (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
Vulnerability is outlined as any defect within the software package, which results attackers to induce access to confidential data. While vulnerabilities in code are well documented very little analysis has been done to find vulnerabilities in design per UML. The presence of vulnerability within the design model of the system makes it necessary to possess a tool that may facilitate developers to avoid or notice them within the design stage Here we describe mechanism to find the defect in system. The tool takes UML Diagram as input. And this metadata (XMI DATA) is cross checked against rule. If the requirement fails to hold then error message is returned.